Increasing Early Growth of Jatropha Cuttings (Jatropha Curca) L.) With The Provision of Organic Growth Regulatory Substance - Bambang Gunawan; Nurul Huda; Yeni Ika Pratiwi (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2021)
Jatropha is a pioneer plant that can easily grow even on marginal lands and has high potential as an oil-producing plant for renewable fuels. This plant is an annual plant that can grow until the age of 50 years, in the form of a bush and begins to produce at 6 months after planting with a productivity varying from 0.5 to 12 tons/ha/year with an oil yield of 25-30% and maximum production will be achieved after planting. Plants 4-6 years old. Jatropha has the potential to become an alternative energy source and become a biofuel with renewable energy sourcesor renewable green energy; in addition to other benefits in traditional medicine for various types of diseases. The purpose of this study was to determine the increase in the initial growth of Jatropha cuttings by giving organic growth regulators. Based on the results of the study, it can be concluded as follows: There was no significant interaction in the treatment combination between the concentration of organic growth regulators and the factor of internode location on all dependent variables observed in the early growth of Jatropha stem cuttings. The internode location factor showed a significant effect on the variable number of leaves, shoot length, root length, number of roots, root wet weight, root dry weight, and the location of the 12th internode (R2) gave better results than the 10th internode location. (R1). The concentration factor of organic growth regulators also showed a significant effect on the variables of leaf number, shoot length, root length, root number, root wet weight, root dry weight and K2 treatment (5 ml per liter of water) gave better and more efficient results. compared to other treatments.